Peran Visi dan Misi Organisasi dalam Membangun Budaya Mutu Pelayanan Kesehatan: Literature Review. - Meutya Zahra Saphira; Nadya Nur Syafina Putri; Acim Heri Iswanto (PrimA: Jurnal Ilmiah Ilmu Kesehatan, 2026)
Introduction: The implementation of strategic management through an organization’s vision and mission is a crucial factor in determining the direction and quality of healthcare services in hospitals. Objective: The objective of this literature review is to analyze the role of an organization’s vision and mission in fostering a culture of quality in healthcare services and to identify the factors that influence their internalization among healthcare workers. Method: The research method used was a literature review, analyzing original research articles from national and international journal databases (such as Google Scholar, PubMed, Garuda and  ScienceDirect) over the past ten years. Results: The review found that vision and mission serve as strategic instruments for fostering a positive work culture, improving compliance with patient safety standards, and strengthening employee engagement. Effective leadership, clear communication, and shared commitment were identified as key factors in translating vision and mission into a sustainable quality culture. Conclusion: In conclusion, strategic alignment between organizational values and field practices is essential for achieving optimal healthcare service quality.